MORPHOTECTONICS OF THE MONGOLIA-SIBERIAN MOUNTAIN BELT - Ufimtsev G.F. (My University, 1990)
The mountains of north-eastern Inner Asia comprise the Mongolia-Siberian orogenic belt which has a complex structure. The southern flank of the belt consists of a chain of large domal uplifts. The Baikal rift zone is located on the northern flank. The central segment is composed of zones of linear warping. The tectonic landforms rest on a large domal basement uplift. The morphology of the latter is paragenetically connected with the shape of the asthenolith underlying the belt. The neotectonic zones are also connected with the deep structure elements.The Mongolia-Siberian mountain belt is a group of orogenic forms typical of intracontinental mountain areas.